IT-based Lean Six Sigma implementation in civil registration: lesson learned from an Indonesian context - Agus Imam Sonhaji; Maria Anityasari; Mahendrawathi ER (Cogent Business & Management, 2024)
This research paper focuses on the integration of Lean Six Sigma (LSS) with Information Technology (IT) in the public sector, specifically in the context of developing countries, using the City Office for Population Administration and Civil Registration (COPACR) in Surabaya, Indonesia, as a case study. Previous studies on this integration have shown positive results, but often lack detailed insights into the implementation process, context, and challenges faced. The paper adopts an action research methodology, observing processes at COPACR through IT, considering the unique challenges of developing countries. The study focuses on the application for birth certificates and follows the DMAIC (Define, Measure, Analyze, Improve, and Control) framework. Key challenges identified include low employee competencies, minimal investment, and a rigid organizational structure. These challenges were measured in the form of speed and quality of services based on the parameters of process capability analysis and Sigma level. Based on the problems identified during the analysis, corrective steps to reduce and eliminate waste were applied for better performance. The system achieved an improved completion time from 17.12 to 0.48 days with the sigma level from -6.46 to 4.09. The sigma level improvement corresponds to an improvement from -2.15 to 1.37 in Cpk parameter. The findings are valuable for public agencies in other cities in Indonesia and developing countries looking to implement IT-based Lean Six Sigma, emphasizing the importance of considering local context and challenges.
Keywords: 650; Action research; IT integration; Lean Six Sigma; public policy; public services